Factors Influencing the Merit System through Spiritual Motivation in the Riau Islands Province - Yeny Trisia Isabella; Chablullah Wibisono; Sri Yanti (PT ARRUS Intelektual Indonesia, 2026)
This study investigates the determinants of the merit system through the mediating role of talent management at the Regional Secretariat of the Riau Islands Province. Specifically, it examines the effects of spiritual motivation, innovative behavior, competence, and work culture on the merit system, both directly and indirectly through talent management. The research employs Structural Equation Modeling using AMOS (SEM-AMOS) to analyze data collected from 160 respondents selected based on the Slovin formula. The findings indicate that spiritual motivation, innovative behavior, and work culture exert a significant positive effect on the merit system, whereas competence demonstrates a positive but statistically insignificant direct effect. All four independent variables significantly influence talent management, which subsequently mediates their relationships with the merit system. The mediation analysis confirms that talent management plays a significant intermediary role, as spiritual motivation, innovative behavior, competence, and work culture each positively and significantly affect the merit system through this mechanism. Additionally, the simultaneous effect of these variables on the merit system via talent management is statistically significant. The coefficient of determination (R²) values demonstrates strong explanatory power, with 0.790 for talent management and 0.886 for the merit system. These results underscore the strategic importance of spiritual motivation, innovative behavior, and work culture in strengthening the merit-based governance of civil servants, particularly when integrated through structured talent management practices. Practically, the study highlights the necessity of embedding cultural and spiritual values, promoting innovation, and enhancing professional competence within public sector human resource management frameworks.